Multi-Channel Packet-Analysis System Based on IEEE 802.15.4 Packet-Capturing Modules - Seong-eun Yoo; Poh Kit Chong; Jeonghwan Bae; Tae-Soo Kim; Hiecheol Kim; Joonhyuk Yoo (International Journal of Distributed Sensor Networks)
There have been increasing demands for research into multi-channel-based wireless sensor network protocols and applications to support requirements such as increased throughput and real-time or reliable transmission. Researchers or developers of these protocols and applications have to simultaneously analyze the exchanged packets for correctness of both their contents and message exchange timelines. However, if developers were to use multiple conventional single-channel packet sniffers for this purpose, debugging during development and the verification process becomes extremely tedious and difficult because of the need to check the correctness of the protocols over multiple channels individually. Therefore, we present a multi-channel packet-analysis system (MPAS) that helps in debugging and verification for multi-channel protocols or applications. Wireless packets are detected and timestamped by each sniffer module in the MPAS for each channel, and packets are preprocessed and transmitted to a GUI-based analyzer, which then parses the received packets and shows them in order. We present the design and implementation results of the MPAS and evaluate its performance by comparing it against a widely used packet sniffer.